IDENTIFIKASI TURUNAN ASAM KARBOKSILAT AKAR Acalypha indica SEBAGAI KANDIDAT INHIBITOR GFAT MELALUI LC-HRMS DAN STUDI IN SILICO - Arviani; K. Salimi, Yuszda; Bialangi, Nurhayati; Chandra Lakasan, Ahmad; Nur Rahman, Zifran (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Diabetes mellitus remains a major global health challenge, prompting the exploration of natural products as sources of safer antidiabetic agents. This study aimed to identify bioactive compounds from the roots of Acalypha indica and evaluate their potential as inhibitors of glutamine–fructose-6-phosphate amidotransferase (GFAT), an enzyme involved in glucose metabolism. Compound profiling was conducted using liquid chromatography–high resolution mass spectrometry (LC-HRMS), while the inhibitory potential against GFAT was assessed through in silico docking. This integrated approach has not been previously reported. Metabolite profiling using LC-HRMS tentatively identified thirteen carboxylic acid derivatives, including hydroxycinnamic acid, gluconic acid, trans-aconitic acid, and glucoheptonic acid. molecular docking analysis revealed strong binding affinities of several compounds toward GFAT. Glucoheptonic acid exhibited the lowest binding energy (−8.0 kcal/mol), followed by xylaric acid A (−7.9 kcal/mol) and trans-aconitic acid (−7.5 kcal/mol). These compounds interacted with key active-site residues Gln421, Ser420, Ser422, and Lys675, suggesting a potential enzyme inhibition mechanism. In silico pharmacokinetic analysis indicated that 2-hexylpentanedioic acid exhibited favorable ADME properties, with high gastrointestinal absorption, no major inhibition of CYP450, and low predicted acute toxicity risk. These findings highlight Acalypha indica roots as a promising source of bioactive carboxylic acid derivatives, with glucoheptonic acid emerging as the most promising candidate for further in vitro evaluation as a GFAT inhibitor